Peranan Bank Dunia terhadap Liberalisasi Pendidikan di Indonesia - Emmy Yunita Aruan; Indra Kesuma Nasution (Universitas Sumatera Utara, 2017)
Indonesia is still experiencing colonialism, it's just a different form of colonization. In the past, we did it with violence or now colonialism is done using a better method of colonialism through economy, culture, education, technology, etc. or in other words, colonialism is called neo liberalism. Indonesia is one of the goals of developed countries to be colonized by using the colonization method of the new model. Some education experts organized by State Universities to become BHMNs carried out by the Government of Indonesia are proof of the colonization of new models in the world of education. Education liberalization is one of the government's policies to improve the education state in Indonesia which is one of the conditions proposed by the World Bank so that Indonesia can be used to help people to develop modalities for increased costs. The role of the World Bank here is to provide loan funds for education in Indonesia. This method is not effective in improving the education system in Indonesia because there are still many people who cannot afford it. This should be the government's attention, because as we do for education, especially in terms of improving lives to be better in order to deal with the turbulence of the development of an increasingly advanced era.